The importance of income-tested benefits in good times and bad: Lessons from EU countries - Chrysa Leventi; Olga Rastrigina; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2016)
Policy over the past years has seen a gradual movement away from universal social benefits towards the provision of more targeted benefit schemes. Using the European tax-benefit microsimulation model EUROMOD, this paper aims to compare the effectiveness of income-tested benefits at different points in the economic cycle. This objective is considered in terms of coverage of households with incomes falling below various thresholds and importance in terms of the fraction of total resources that these benefits provide. The prevalence and relative weight of income-tested benefits throughout the income distribution is also examined. We compare the situation in 2009 with that in 2014 (or 2013) for fifteen EU Member States experiencing differing economic conditions over the period in question, including those which have been affected comparatively little by the crisis as well as those which have witnessed severe reductions in economic activity and employment levels and those in strong recovery by 2014. As EU-SILC micro-data containing household income for 2013 or 2014 are not available yet, standard EUROMOD routines are enhanced with additional adjustments to the EU-SILC based input data in order to take into account changes in the labour market. We attempt to indicate the sensitivity of the estimated policy effectiveness indicators to these particular changes. We conclude by discussing the methodological pitfalls and main findings of this research.
Keywords: H53; I38; D3; 330; income-tested benefits; coverage; economic cycle; EU; microsimulation